Impact of fish species and processing technology on minor fish oil components. (March 2017) - Merkle, Sybille; Giese, Editha; Rohn, Sascha; Karl, Horst; Lehmann, Ines; Wohltmann, Andreas; Fritsche, Jan
Abstract: Fish and fish oil are an important source of essential dietary components such as polyunsaturated long chain fatty acids like eicosapentaenoic acid and docosahexaenoic acid. Refining of crude fish oil is necessary to remove environmental contaminants e.g., dibenzo- p -dioxins, dibenzofurans, dioxin-like polychlorinated biphenyls, and non-dioxin-like polychlorinated biphenyls for reaching legal limits, ensuring a pleasant taste and for enhancing shelf-life. However, during the deodorization of crude fish oil, process contaminants such as 2- and 3-monochloropropane-diol esters and glycidyl esters may be formed. The aim of the present study was to provide a comprehensive overview on the content of selected environmental and process contaminants in raw and processed fish oils deriving from different fish species. In crude fish oils extracted from farmed fish, the contents of environmental contaminants were well below the legal limits for food grade fish oil. In contrast, fish oils extracted from captured fish did not meet the requirements for human consumption. When applying filtration over active carbon, a reduction in the content of dibenzo-p-dioxins, dibenzofurans and dioxin-like polychlorinated biphenyls was achieved. 2- and 3-monochloropropane-diol ester and glycidyl ester contents were considerably higher in the refined compared to the crude fish oils investigated. Additionally, the comparison of analyzed and labeled contents of polyunsaturated long chain fatty acids showed a satisfying compliance. Graphical abstract: Highlights: Refining of crude fish oil is necessary to remove environmental contaminants. Process contaminants may be formed during the deodorization of fish oil. The content of PCDD/F and dl-PCBs could be reduced by active carbon filtration. 2- and 3-MCPD ester and glycidyl ester contents were higher in refined fish oils. Analyzed and labeled contents of n-3 PUFA showed satisfying compliance.